The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.48550/arxiv.2104.06367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensing quantum chaos through the non-unitary geometric phase

Abstract: Quantum chaos is usually characterized through its statistical implications on the energy spectrum of a given system. In this work we propose a decoherent mechanism for sensing quantum chaos. The chaotic nature of a many-body quantum system is sensed by studying the implications that the system produces in the long-time dynamics of a probe coupled to it under a dephasing interaction. By introducing the notion of an effective averaged decoherence factor, we show that the correction to the geometric phase acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Also, we have analyzed the mixing of the redundant records by allowing intra-environment interactions. Despite low disorder is associated to an ergodic dynamics and ergodicity usually yields to a markovian evolution [15], we have found that a highly disordered evolution is less harmful for the appearance of classical objectivity. Hence, a high amount of disorder is not only beneficial for the initial state under consideration but also reduces the mixing of the redundant records in the presence of intra-environment interactions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Also, we have analyzed the mixing of the redundant records by allowing intra-environment interactions. Despite low disorder is associated to an ergodic dynamics and ergodicity usually yields to a markovian evolution [15], we have found that a highly disordered evolution is less harmful for the appearance of classical objectivity. Hence, a high amount of disorder is not only beneficial for the initial state under consideration but also reduces the mixing of the redundant records in the presence of intra-environment interactions.…”
Section: Discussionmentioning
confidence: 68%
“…In general, QD has been studied in the simplest scenario, where the fragments of the environment do not interact with each other. However, this may not be the most realistic situation in an experimental setup, where the intrinsic dynamics of the environment can play a significant role in the decoherent dynamics of the open system [14,15]. For this reason, it is essential to understand how different environmental properties influence the emergence of QD and which are the mechanisms that may enhance the proliferation of redundancy.…”
Section: Introductionmentioning
confidence: 99%